Pengaruh Independensi, Tingkat Pendidikan dan Keahlian Profesional Terhadap Kinerja Pengawas Pada Lembaga Perkreditan Desa (LPD) di Kecamatan Abiansemal - Artini, Ni Putu Septa; Putra, I Putu Deddy Samtika; Putra, I Made Endra Lesmana (Hita Akuntansi dan Keuangan, 2025)
The outcome of a supervisor's efforts in both quantity and quality while executing the responsibilities and powers assigned to them is their supervisory performance. The degree of education, professional expertise, and independence are some of the variables that can impact a supervisor's success. This study purpose to ascertain the impact of supervisor performance at Village Credit Institutions (LPD) in Abiansemal District on factors such as independence, educational attainment, and professional expertise. The study's population consists of all active LPD supervisors in the Abiansemal sub-district, which has 32 LPDs and 140 supervisors overall. The sampling technique is a non-probability sampling method using a saturated sampling technique. The sample used was 140 respondents obtained through a data collection method by distributing questionnaires measured using Likert scales. The data analysis technique uses Smart PLS 4.1.0. The study's findings demonstrate that the performance of LPD pupils is significantly improved by independence, education level, and professional expertise.